Study of BMP15 gene polymorphism in Boer, Kacang, and Boerka goats - Aron Batubara; Simon Elieser; Cece Sumantri (Indonesian Center for Animal Research and Development (ICARD), 2016)
The bone morphogenetic protein 15 (BMP15) gene or commonly called FecX (fecundity chromosome X) is a gene that controls the prolific properties. This study aims to identify the mutation of BMP15 gene and to analyze its polymorphism in Boer, Kacang, and Boerka goats. The total of 50 female goat bloods were identified using PCR-Sequencing method, 17 Boer, 16 Kacang and 17 Boerka respectively. BMP15 gene amplification resulted fragment with the length of 141 bp. Genotyping of BMP15 gene produced three genotypes. The result showed that BMP15 gene found two polymorphic SNP were analyzed by genotype frequency, allele frequency, heterozygosis and equilibrium of genotype in all population was detected by the Hardy-Weinberg equilibrium test (χ2). Sequence analysis results of BMP15 gene showed that there were two mutation between adenine (A) and guanine (G) bases and determination of genotype BMP15 gene produces three genotypes showed that there were GG, GA and AA. In conclusion, there was found the mutation of BMP15 gene in Boer, Kacang and Boerka goats and genetic polymorphism were identified using PCR-Sequencing method.